Clinical usefulness of magnetic resonance imaging in multiple system atrophy. Issue 1 (1st July 1998) - Schrag, A; Kingsley, D; Phatouros, C; Mathias, C J; Lees, A J; Daniel, S E; Quinn, N P
Abstract : OBJECTIVES: To determine the sensitivity, specificity, and positive predictive values of a selection of abnormal findings in the putamen and infratentorial structures on routine magnetic resonance imaging for distinguishing between multiple system atrophy, idiopathic Parkinson's disease, and age matched controls. PATIENTS AND METHODS: Two neuroradiologists blindly and independently rated axial T2 weighted and proton density MRI of 44 patients with multiple system atrophy, 47 patients with idiopathic Parkinson's disease, and 45 controls. High field (1.5 T) scans were available in 16 patients with multiple system atrophy, 15 patients with idiopathic Parkinson's disease, and 16 controls. All other patients had 0.5 T scans. RESULTS: On both 0.5 and 1.5 T scans the following items had high specificity but low sensitivity: putaminal atrophy, a hyperintense putaminal rim, and infratentorial signal change. Finding any infratentorial abnormality gave higher sensitivity but lower specificity. Putaminal isointensity or hypointensity relative to globus pallidus, absolute putaminal hypointensity, and altered size of the olives were not useful discriminators. The overall sensitivity was 73% on 0.5 T and 88% on 1.5 T scans. The specificities of these findings for multiple system atrophy in comparison to idiopathic Parkinson's disease and controls on 0.5 T were 95% and 100% respectively, and on 1.5 T were 93% and 91% respectively. Finding any of the described abnormalities on MRI gave a positive predictive value of 93% on the 0.5 T machine, and 85% on the 1.5 T scanner.